ISIS Terror on detik.com Online Media in Indonesia - Ribut Priadi; Syukur Kholil; Iskandar Zulkarnain (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Bomb explosions carried out by the ISIS network in Indonesia attracted the attention of the mass media, both local, national and international, including detik.com and republika.co.id. In covering the events, each media had a different perspective so that gave birth to the tendency in the news. Framing reporting aims to make the audience also have a similar tendency to the media read. The purpose of this study is: To find out the tendency of reporting on ISIS by detik.com and its implications for the reader's perception of the Islamic state. This study uses a qualitative approach with a type of descriptive research that aims to explain the implications of detik.com framing related to ISIS terrorism news in Indonesia, especially regarding audience perceptions about the Islamic Caliph. Media framing was carried out through the analysis of Zondang Pan and Kosicki. For framing effects the reception theory is used. The speakers were activists of Islamic Student Organizations, IMM, KAMMI, HMI, HIMMAH and PMII. The results showed that detik.com's readers' perception of the Islamic State was a positive concept, but it did not have to be realized in a formal or forced form, especially in Indonesia. Detik.com readers also view the concept of Islamic sharia as something positive, but not made in formal form through statutory regulations. In detik.com news, it is more likely to be neutral by submitting field facts and opinion facts in the news without relating to matters related to Islam.